Pravastatin polarizes the phenotype of macrophages toward M2 and elevates serum cholesterol levels in apolipoprotein E knockout mice. Issue 8 (August 2018) - Zhang, Xiaoling; Xiao, Shengjun; Li, Quanzhong
Objective: Statins are clinically used for protection against cardiovascular disease with lipid-lowering and anti-inflammatory properties. These properties tip the balance of macrophage polarization, which is an essential process in the development and progression of atherosclerosis. This study aimed to investigate the effect of pravastatin on atherosclerosis of the aorta in apolipoprotein E knockout (apoE-KO) mice without high lipid feeding. Methods: Six 8-week-old apoE-KO male mice were randomly divided into two groups: a control group and a pravastatin (40 mg·kg −1 ·day −1 )-treated group. At 35 weeks, the mice were sacrificed and the size of plaques on the aorta was assessed by Oil Red O staining. M1 and M2 macrophages were identified by inducible nitric oxide synthase and arginase-I, respectively, using immunohistochemistry. Results: Pravastatin increased the size of atherosclerotic plaques in apoE-KO mice without high lipid feeding. The ratio of M1/M2 macrophages increased in atherosclerotic plaques, which might slow the process of atherosclerosis, while blood cholesterol levels were elevated. Conclusion: Our study suggests that pravastatin polarizes the phenotype of macrophages toward M2 in atherosclerotic lesions, despite an increase in serum cholesterol levels in ApoE-KO mice.